Development of Human ILCs and Impact of Unconventional Cytotoxic Subsets in the Pathophysiology of Inflammatory Diseases and Cancer - Calvi, Michela; Di Vito, Clara; Frigo, Alessandro; Trabanelli, Sara; Jandus, Camilla; Mavilio, Domenico (Frontiers in Immunology, 2022)
Innate lymphoid cells (ILCs) were firstly described by different independent laboratories in 2008 as tissue-resident innate lymphocytes mirroring the phenotype and function of T helper cells. ILCs have been subdivided into three distinct subgroups, ILC1, ILC2 and ILC3, according to their cytokine and transcriptional profiles. Subsequently, also Natural Killer (NK) cells, that are considered the innate counterpart of cytotoxic CD8 T cells, were attributed to ILC1 subfamily, while lymphoid tissue inducer (LTi) cells were attributed to ILC3 subgroup. Starting from their discovery, significant advances have been made in our understanding of ILC impact in the maintenance of tissue homeostasis, in the protection against pathogens and in tumor immune-surveillance. However, there is still much to learn about ILC ontogenesis especially in humans. In this regard, NK cell developmental intermediates which have been well studied and characterized prior to the discovery of helper ILCs, have been used to shape a model of ILC ontogenesis. Herein, we will provide an overview of the current knowledge about NK cells and helper ILC ontogenesis in humans. We will also focus on the newly disclosed circulating ILC subsets with killing properties, namely unconventional CD56dim NK cells and cytotoxic helper ILCs, by discussing their possible role in ILC ontogenesis and their contribution in both physiological and pathological conditions.